2021
DOI: 10.3390/jcm10081779
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chronic Tinnitus in Noise-Induced Hearing Loss and Presbycusis

Abstract: The most frequent causes of tinnitus associated with hearing loss are noise-induced hearing loss and presbycusis. The mechanism of tinnitus is not yet clear, although several hypotheses have been suggested. Therefore, we aimed to analyze characteristics of chronic tinnitus between noise-induced hearing loss and presbycusis. Materials and Methods: This paper is a retrospective chart review and outpatient clinic-based study of 248 patients with chronic tinnitus from 2015 to 2020 with noise-induced or presbycusis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The mean tinnitus frequency of our cohort was 5072 Hz, similar to that of Brueggemann et al (5058 Hz) [ 12 ]. Kang et al [ 30 ] found a lower tinnitus frequency (4973 Hz) in patients with age-related hearing losses and a higher tinnitus frequency (5636 Hz) in subjects with noise-induced hearing losses. The mean tinnitus frequency was higher for the male and NH subgroups but lower for the female subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The mean tinnitus frequency of our cohort was 5072 Hz, similar to that of Brueggemann et al (5058 Hz) [ 12 ]. Kang et al [ 30 ] found a lower tinnitus frequency (4973 Hz) in patients with age-related hearing losses and a higher tinnitus frequency (5636 Hz) in subjects with noise-induced hearing losses. The mean tinnitus frequency was higher for the male and NH subgroups but lower for the female subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, it is likely that some participants in the exposed group, especially those with the highest occupational noise exposure scores, had some degree of undiagnosed NIHL. NIHL, which typically manifests as elevated hearing thresholds secondary to OHC loss, is thought to be strongly associated with tinnitus ( Boger et al, 2016 ; Dias et al, 2006 ; Kang et al, 2021 ; Mrena et al, 2007 ; Yankaskas, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who experience tinnitus commonly describe it as constant and irritating sounds in the ears that can make it difficult to concentrate, to understand what people are saying, and to hear external sounds (Langguth et al, 2019; Tang et al, 2019). Tinnitus can have various etiologies, many of which are closely tied to neurological insult and hearing loss; common examples include sensorineural hearing loss (Kaltenbach, 2011), noise induced hearing loss (Kaltenbach et al, 2000), presbycusis (Kang et al, 2021), ototoxicity from oral medications (Cianfrone et al, 2011), neurologic and vestibular disorders, and infectious disease (Langguth et al, 2019). Tinnitus affects 21.4 million adults (9.6%) in the United States, a third of whom experience near-constant symptoms (Bhatt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%